Analisis Kualitas Manajemen Pembelajaran Karya Sastra Puisi Santri melalui Pendekatan Estetika Islam dan Indikator Literasi Bahasa Indonesia - Nurharini, Firdausi; Munawwaroh, Munawwaroh (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
This study analyzes the quality of poetry literary learning management for santri (Islamic boarding school students) at Pondok Pesantren Putri Salafiyah 2 Bangil, utilizing an Islamic aesthetic approach and Indonesian literacy indicators. Employing a descriptive quantitative approach, the research population comprised santri actively engaged in poetry learning and competitions at Pondok Pesantren Putri Salafiyah 2 Bangil , with a purposive sample of 25 santri. Data were collected through documentation of poetry score recapitulation, structured observation based on 20 assessment indicators (originality, expression, diction, phonology, rhyme, Islamic aesthetics, etc.), and a 1-5 scale assessment questionnaire (rubric). The instrument demonstrated high reliability with a Cronbach’s Alpha of 0.90, indicating strong internal consistency. The findings reveal that poetry learning management has been effective and of high quality, reflected in an average total score of 78.3 points for santri, with most scores falling within the good category (75-85 points). Santri exhibited strong proficiency in Islamic aesthetic aspects, such as originality of ideas and powerful expression of Islamic values, as well as Indonesian literacy indicators like diction and the ability to evoke emotions. Top-scoring participants (A: 100, C: 99, D: 93) successfully integrated religious aesthetics and language literacy structures harmoniously. However, some santri still require reinforcement in technical linguistic aspects, particularly rhyme patterns and inter-line consistency. A positive correlation was found between Islamic aesthetic ability and language literacy levels, suggesting that an aesthetic approach enriches content while strengthening language proficiency. This study recommends continuous educator training and facilitating creative expression opportunities to enhance the quality of santri poetry learning.